2022
DOI: 10.1007/s00167-022-07036-w
|View full text |Cite
|
Sign up to set email alerts
|

Medial congruent polyethylene design show different tibiofemoral kinematics and enhanced congruency compared to a standard symmetrical cruciate retaining design for total knee arthroplasty—an in vivo randomized controlled study of gait using dynamic radiostereometry

Abstract: Purpose New total knee arthroplasty implant designs attempt to normalize kinematics patterns that may improve functional performance and patient satisfaction. It was hypothesized that a more medial congruent (MC) anatomic bearing design (1) inluences the tibiofemoral kinematics and (2) enhances articular congruency compared to a standard symmetrical cruciate retaining (CR) bearing design. Methods In this double-blinded randomized study, 66 patients with knee osteoarthritis were randomly included in two groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The clinical application of the precise, accurate and radiation low‐dose dRSA imaging method for the assessment of knee kinematics with the pivot‐shift test is limited to small‐scale experimental or clinical studies, such as for evaluating new surgical methods [3, 10, 21, 22, 39, 40, 48]. There are several reasons, including that image analyses are user‐intensive, and there is a need for a surgeon/specialist to perform the pivot‐shift test during imaging with radiation dose being applied to the surgeon's hands (although minimised with the use of lead gloves).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical application of the precise, accurate and radiation low‐dose dRSA imaging method for the assessment of knee kinematics with the pivot‐shift test is limited to small‐scale experimental or clinical studies, such as for evaluating new surgical methods [3, 10, 21, 22, 39, 40, 48]. There are several reasons, including that image analyses are user‐intensive, and there is a need for a surgeon/specialist to perform the pivot‐shift test during imaging with radiation dose being applied to the surgeon's hands (although minimised with the use of lead gloves).…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al reported better sagittal stability using an MC insert [11]. Petersen et al [18], Shi et al [21] and Cacciola et al [4] also report better stability and excellent clinical and patient reported outcomes in patients undergoing TKA using a medial pivot insert. Sabatini et al [20] similarly reported good to excellent results using a third‐generation prosthesis system with a MC polyethylene insert.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported on the rationale behind the evolution of the MC polyethylene insert design in providing a greater level of stability with minimum constraint [9, 18, 21]. Alesi et al [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional evidence from Sun et al 10 and Konno et al 11 indicates that congruent inserts decrease patellofemoral pressures, mimic near-normal joint kinematics, and reduce the risk of patellofemoral complications. Enhanced anteroposterior stability is a distinct advantage of the MC articulation, which also diminishes the likelihood of anterolateral pain post-TKA 7,12,13 . Nishio et al 14 conducted an investigation utilizing a CT-based navigation system to examine intraoperative kinematics, finding that PROMs, including functional activities and patient satisfaction, fared better with a medial pivot insert.…”
Section: Manuscriptmentioning
confidence: 99%